2001
DOI: 10.1111/j.1095-8649.2001.tb02373.x
|View full text |Cite
|
Sign up to set email alerts
|

The dorso‐lateral pit organs of the Port Jackson shark contribute sensory information for rheotaxis

Abstract: Resting Port Jackson sharks Heterodontus portusjacksoni with dorso-lateral pit organs ablated oriented with a mean angle of 263 to the current direction in a flume. This was significantly different (P<0·01) to controls (normal and sham operated) who had a pooled mean angle of 44 to the current. Thus the dorso-lateral pit organs of H. portusjacksoni, like the free neuromasts of some teleosts, provide sensory information for rheotaxis. 2001 The Fisheries Society of the British Isles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…In addition, Arnold (Arnold, 1969) provides some evidence that benthic flatfish (Pleuronectes platessa) also rely on lateral line information, as rheotactic responses were observed in the dark at flow speeds that did not displace the fish downstream. Similarly, epaulette sharks (Hemiscyllium ocellatum) exhibit rheotaxis when they are located on the benthos, but not when they are higher in the water column (Peach, 2001). Finally, our blind cavefish results are consistent with the absence of lateral line effects observed in other species with non-sedentary behaviors, such as the surface-dwelling giant danio (Bak-Coleman et al, 2013).…”
Section: Comparisons With Other Speciesmentioning
confidence: 99%
“…In addition, Arnold (Arnold, 1969) provides some evidence that benthic flatfish (Pleuronectes platessa) also rely on lateral line information, as rheotactic responses were observed in the dark at flow speeds that did not displace the fish downstream. Similarly, epaulette sharks (Hemiscyllium ocellatum) exhibit rheotaxis when they are located on the benthos, but not when they are higher in the water column (Peach, 2001). Finally, our blind cavefish results are consistent with the absence of lateral line effects observed in other species with non-sedentary behaviors, such as the surface-dwelling giant danio (Bak-Coleman et al, 2013).…”
Section: Comparisons With Other Speciesmentioning
confidence: 99%
“…2). Their identity as lateral line organs was only recently confirmed by morphological and behavioral studies (Peach and Rouse, 2000;Peach, 2001).…”
Section: Introductionmentioning
confidence: 93%
“…These studies indicated that among teleosts there is a diverse set of morphological features and distribution patterns [e.g., Münz, 1979Münz, , 1989Coombs et al, 1989;Song and Northcutt, 1991;Coombs and Montgomery, 1994]. Similar assertions could be described for non-teleost fishes [Webb and Northcutt, 1997;Maruska and Tricas, 1998;Maruska, 2001;Peach, 2001Peach, , 2003. Few data are available for the sea bass lateral line system [Diaz et al, 2003;Faucher et al, 2003].…”
Section: Introductionmentioning
confidence: 94%